Loss of Vagal Sensitivity to Cholecystokinin in Rats Born with Intrauterine Growth Retardation and Consequence on Food Intake - Ndjim, Marième; Poinsignon, Camille; Parnet, Patricia; Le Dréan, Gwenola (Frontiers in Endocrinology, 2017)
Perinatal malnutrition is associated with low birth weight and an increased risk of developing metabolic syndrome in adulthood. Modification of food intake (FI) regulation was observed in adult rats born with intra-uterine growth retardation (IUGR) induced by maternal dietary protein restriction during gestation and maintained restricted until weaning. Gastrointestinal peptides and particularly cholecystokinin (CCK) play a major role in short term regulation of food intake by relaying digestive signals to the hindbrain via the vagal afferent nerve (VAN). We hypothesized that vagal sensitivity to CCK could be affected in rats suffering from undernutrition (low protein, LP) during fetal and postnatal life, leading to an altered gut-brain communication and impacting satiation. Our aim was to study short-term FI along with signals of appetite and satiation in adult LP rats compared to control rats. The dose response to CCK injection was investigated on FI as well as the associated signaling pathways activated in nodose ganglia. We showed that LP rats have a reduced first-meal satiety ratio after a fasting period associated to a higher postprandial plasmatic CCK release, a reduced sensitivity to CCK when injected at low concentration and a reduced presence of CCK1-receptor in nodose ganglia. Accordingly, the lower basal and CCK-induced phosphorylation of CaMKII in nodose ganglia of LP rats could reflect an under-expressed vanilloid family of transient receptor potential (TRPV) cation channels on VAN. Altogether, the present data demonstrated a reduced vagal sensitivity to CCK in LP rats at adulthood, which could contribute to deregulation of food intake reported in this model.